2006
DOI: 10.1128/jcm.44.4.1547-1549.2006
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of Clinical Microbiology Laboratories in the United States with Current Recommendations for Processing Respiratory Tract Specimens from Patients with Cystic Fibrosis

Abstract: Respiratory tract specimens from patients with cystic fibrosis (CF) require unique processing by clinical microbiology laboratories to ensure detection of all potential pathogens. The present study sought to determine the compliance of microbiology laboratories in the United States with recently published recommendations for CF respiratory specimens. Microbiology laboratory protocols from 150 of 190 (79%) CF care sites were reviewed. Most described the use of selective media for Burkholderia cepacia complex (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…As a result, the US Cystic Fibrosis Foundation recommended that disk diffusion or E-test be the method of choice for susceptibility testing of this organism [15]. However, in a recent survey of microbiology laboratories servicing US CF centers, only a little over half (52%) were following this recommendation [16].…”
Section: For Reprint Orders Please Contact: Reprints@future-drugscommentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the US Cystic Fibrosis Foundation recommended that disk diffusion or E-test be the method of choice for susceptibility testing of this organism [15]. However, in a recent survey of microbiology laboratories servicing US CF centers, only a little over half (52%) were following this recommendation [16].…”
Section: For Reprint Orders Please Contact: Reprints@future-drugscommentioning
confidence: 99%
“…Unfortunately, practices in the clinical microbiology laboratory have not kept pace, as evidenced by close to half of the laboratories performing P. aeruginosa susceptibility testing using methods associated with very major errors [13,16]. With increasing use of aerosolized therapy, laboratories must be able to provide susceptibility results for both tobramycin and colistin at both aerosol-and serum-achievable levels.…”
Section: For Reprint Orders Please Contact: Reprints@future-drugscommentioning
confidence: 99%
“…Several studies have shown that conventional biochemical tests can misidentify B. cepacia complex species, biochemical inactive and newly emerging CF pathogens [6,33]. Thus, laboratories processing CF specimens need access to molecular identification tools and/or in equivocal cases the possibility to send specimens and/or isolates to national or international referral laboratories on CF microbiology [34]. Services regarding the genomic species identification of B. cepacia complex isolates are available by the European Burkholderia cepacia complex…”
Section: Columbia Colistin-nalidixic Acid Agar Lipase-salt-mannitol mentioning
confidence: 99%
“…and Aspergillus spp.). 41 Thus, the majority of clinical laboratories processing the CF respiratory tract specimens have standardized their techniques, use appropriate selective media and prolonged incubation, and identify gram-negative organisms to the species level. The CF Foundation recommends continued use of the methods described in the 2003 Infection Control Guideline for CF for when to perform respiratory tract cultures, how to transport specimens, and the use of selective media.…”
Section: Leisure Activitiesmentioning
confidence: 99%